ROLE OF GSK-3 IN Wnt/β-CATENIN SIGNALING PATHWAY IN OBESITY - A. S. Kulakova; I. A. Snimshchikova; M. O. Plotnikova (Медицинская иммунология)
The complexity of the adipogenesis mechanism results from the impact of multiple cues, among which an important place is held by the components of the Wnt signaling pathway. The search for potential markers of the development of diseases related to obesity aroused an interest in the study of GSK-3 (glycogen synthase kinase), β-catenin. GSK-3β is an intracellular serine / threonine kinase found in the cytoplasm, nucleus, mitochondria, synthesized in all body tissues and involved in regulating metabolic processes, cell proliferation, apoptosis etc. The first of the discovered functions of GSK-3β was the regulation of glycogen synthesis. Active GSK-3β phosphorylates and thereby inhibits glycogen synthase. As a result of the insulin binding to the cell receptor via inositol-3-phosphate, protein kinase B (Akt1) is activated, which, in turn, phosphorylates and inhibits GSK-3β. In addition, GSK-3β is involved in the regulating glucose metabolism. The most important function of GSK-3β is the inhibition of the β-catenin protein. In a resting cell, GSK-3β in complex with the APC and Axin proteins binds and phosphorylates the β-catenin transcription factor, which leads to its ubiquitination and degradation. When Wnt proteins act on the cell, the Dvl protein is activated, which, by binding to GSK-3β, releases β-catenin, preventing its degradation, however, the role of GSK3α/β in the adipocyte inflammatory response has not yet been fully investigated, therefore it seems promising to study the role of GSK-3 in the Wnt/β-catenin signaling pathway in obesityThe aim of the study was to assess the activity of the components of the Wnt signaling pathway in obese patients by measuring the serum level of GSK-3 and β-catenin. There were enrolled 32 patients with progressive forms of I-III degree obesity in the absence of diabetes mellitus. The concentration of serum GSK-3α, GSK-3β, and β-catenin was measured by enzyme-linked immunoassay. Data are presented as absolute and relative (%) number of patients; arithmetic mean; medians, 1 and 3 quartiles – Ме (Q0.25-Q0.75). Obese patients contained a 7.5-fold increased serum level of GSK-3α (785 (371-1317.5) pg/ml) compared to healthy individuals 105 (102.5-110) pg/ml, (p < 0.001), paralleled with increased amount of GSK-3β, which level in obese patients was 295 (190-695) pg/ml, which is by 18.3% higher than those in healthy individuals 241 (218.75-287.5) pg/ml, p = 0.111. Amount of GSK-3 depending on the degree of obesity tended to increase, most often coupled to decreased β-catenin level which is consistent with the literature data and can be considered as a prognostic criterion for the course of pathological processes in obesity.